2017
DOI: 10.5116/ijme.5898.2f91
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of script concordance tests in fourth-year medical students

Abstract: ObjectivesThis investigation aimed to determine the validity of script concordance test (SCT), compared with clinical-case-related short-answer management problems (SAMP), in fourth-year medical students. MethodsThis retrospective study was conducted at the Medical School of Lille University. Cardiology and gynecology examinations both included 3 SCT and 2 clinical-case-related SAMP.  Final score did not include SCT results, and was out of 20 points. The passing score was ≥10/20. Wilcoxon and McNemar tests we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
(25 reference statements)
0
3
0
1
Order By: Relevance
“…As healthcare becomes increasingly complex, developing and assessing clinical reasoning skills becomes critical. The SCT could serve as an effective method to achieve this, complementing traditional assessment tools and providing a more nuanced understanding of a student's learning progress [34][35][36][37][38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…As healthcare becomes increasingly complex, developing and assessing clinical reasoning skills becomes critical. The SCT could serve as an effective method to achieve this, complementing traditional assessment tools and providing a more nuanced understanding of a student's learning progress [34][35][36][37][38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Un estudio con carácter nacional implementado en Francia y dirigido a medicina interna, analizó la correlación de los puntajes obtenidos en tareas de RC a través de pruebas de selección múltiple y scripts, determinando una elevada asociación entre ambos (Cohen-Aubart et al, 2021). Otra investigación centrada en cuarto año de medicina, describió heterogeneidad en los puntajes de scripts cuando se compararon con la resolución de situaciones clínicas breves, sugiriendo utilizarlos solo con fines formativos (Nseir, Elkalioubie, Deruelle, Lacroix y Gosset, 2017). Dicha observación se asimila a recomendaciones previas (Arceo y Durante, 2013).…”
Section: Discussionunclassified
“…This study showed relatively high internal reliability coefficient for this test (.74). A good test reliability for SCT is 0.7 to 0.8 (18, 26, 29), and different studies have reported different internal consistency coefficients as Cronbach's alpha of 0.78 (1), 0.745 (23), 0.73 (32), .85 (30), 0.79 (21), 0.73 (31), .8 (28), 0.9 (19). Andrew et al stated that based on SCT 3 or 5 test options, Cronbach's alpha coefficient varies from 0.78 to 0.68 (33).…”
Section: Discussionmentioning
confidence: 99%
“…SCT is used in various fields of medical education (13, 18-23), nevertheless, to our knowledge, its application in the field of midwifery training has not still been investigated or published in English or Persian languages. However, an article was published in French language about application of SCT in midwifery (24, 25).…”
Section: Introductionmentioning
confidence: 99%